Análise da potabilidade e da toxicidade de amostras de água da cidade de Itabira (MG) por meio de uma sequência de ensino - Érica Vitória de Souz (2022)
There are many motivations for approaching the theme “Water” in basic education. It is part of the composition of all living beings, enabling the occurrence of biochemical reactions essential to life. Its current scarcity and low quality have negatively affected the lives of many people around the world. The municipality of Itabira (MG) has gone through recurrent drinking water supply problems, and, therefore, this was the motivation for the development of this research. Its objective is to develop an investigative teaching sequence (ITS) on the quality of water in different parts of that city. It also aims to promote the scientific training of high school students. To integrate the ITS, experimental tests of water potability and toxicity were developed by the researcher professor. In these tests, 11 water samples from different parts of the city were analyzed with a commercial potability kit (Alfakit). These samples were also submitted to phytotoxicity tests with lettuce seeds (Lactuca sativa). The proposed investigative teaching activity was evaluated according to the Diagnosis of Elements of Science Teaching by Investigation (DESTI) tool developed and validated by Cardoso and Scarpa (2018). This evaluation showed the potential of the teaching sequence to generate opportunities for students to engage in the practices that the scientific community uses to generate and validate knowledge. data processing, as well as the communication of the results obtained